The ground state of (He-H-He)(+) from correlated ab initio calculations - Komasa, Jacek; Rychlewski, Jacek (POLISH CHEMICAL SOCIETY, 1998)
He2H+ ion in its ground state is studied by means of ab initio methods taking into account the electron correlation. Geometry optimization at the CCSD(T)/cc-pV5Z level of theory has been performed and the potential energy hypersurface scan is presented. The optimum conformation is linear and symmetric with the proton at the He-He midpoint and the He-H distance equal to 1.75 bohr. Stabilization energy with respect to the He2H+ --> HeH+ + He dissociation channel has been computed. Additionally, a single point variational calculations with the use of the Exponentially Correlated Gaussian wave functions have been performed. They supply an upper bound to both the total electronic energy (-5.903505 hartree) and the stabilization energy (-13.224 kcal/mol). A comparison of the results from both the perturbational coupled cluster and variational methods is presented.
Keywords: Helium dimer; Exponentially correlated Gaussian functions